Improvement of Mro Material Procurement Efficiency Through the Six Sigma Concept at PT Krakatau Steel (Persero) TBK - Wahyu Wijanarko (Jurnal Indonesia Sosial Teknologi, 2024)
PT Krakatau Steel (Persero) Tbk (PTKS) is a State-Owned Enterprise engaged in the production of steel and related services. The MRO Procurement Department is a procurement function to process MRO Material purchasing at PTKS. The main problem currently faced is the lead time for the MRO material procurement process which takes a long time, the reason is that procurement is often conducted by spot method and repeatedly for the same material. Too long lead times pose a risk to the smooth production process due to the unavailability of MRO materials when needed. Referring to the MRO Procurement Department's KPI, >85% of the number of POs (Purchase Orders) issued must have a lead time of <41 days, however, based on the actual historical data for 2022, the PO lead time achievement for the MRO material procurement process does not meet the target. Department's KPI, >85% of the number of PO’s (Purchase Orders) issued must have a lead time of <41 days, however, based on the actual historical data for 2022, the PO lead time achievement for the MRO material procurement process does not reach the target. An alternative solution used to speed up procurement lead times is implementing a Blanket Purchase Agreement (BPA) and/or Consignment Contract for MRO routine/consumable material types. The results obtained are that the long and complicated MRO material procurement process for the same type of material can be eliminated, which means that with the improvements made, the MRO Procurement Department can implement a more efficient procurement process.